Ultrasonic shear wave elastography for compliance-weighted-imaging - Rengaraju, V.; Kargel, Ch; Sack, Ingolf (2012 IEEE I2MTC - International Instrumentation and Measurement Technology Conference, Proceedings, 2012)
Ultrasonic shear wave elastography is a dynamic method that allows in-vivo measurement of the shear elasticity of human tissue. Recovering elasticity maps from time-harmonic wave data remains a major challenge since the calculation of spatially resolved elasticity parameters encounters ill-posed inverse problems due to noise and unknown boundary conditions. Therefore, compliance-weighted- imaging (CWI) is introduced to ultrasonic shear wave elastography for the measurement of elasticity ratios and the visualization of elastic heterogeneities by the amplitude alteration of harmonic shear strain due to wave scattering. In this paper, the results of experiments performed on tissue-mimicking phantoms comprising a planar interface between the hard and soft compartments, and a soft cylindrical inclusion embedded in stiffer background are shown and compared to theoretical models. The proposed ultrasound based CWI method is potentially interesting for the detection of pathological lesions such as medical applications. © 2012 IEEE.
CRIS-Team Scopus Importer:2022-08-03
Keywords: compliance weighted imaging; shear horizontal scattering; shear vertical scattering; shear wave elastography; tumor detection; ultrasonic elasticity imaging